Analysis of Labor Fulfillment to Improve Customer Satisfaction - Mendrofa, Syah Abadi; Lisbet, Zeanette T.; Mukaromah, Hajar; Iswanto, Iswanto; Utomo, Bekti (Civiliza Publishing, 2024)
This research project aims to examine how the fulfillment of the workforce can enhance customer satisfaction through a comprehensive analysis of existing literature in the field. The objective of this study is to examine the relationship between the quantity, quality, and distribution of the workforce and the level of customer satisfaction. Previous research indicates that ensuring the optimal quantity, skill level, and strategic placement of the workforce can enhance service performance and, subsequently, customer satisfaction. Additionally, workforce training and development, as well as an effective performance management system, are vital in developing a workforce equipped to address customer needs.